Answer to Question #247050 in Differential Equations for Sarah

Question #247050

(xΒ³-y)dx+xdy=0


1
Expert's answer
2021-10-06T06:16:42-0400

Let us solve the differential equation "(x\u00b3-y)dx+xdy=0," which is equivalent to "xy'-y=-x^3" and to "\\frac{y'}x-\\frac{y}{x^2}=-x" after dividing by "x^2." It follows that "(\\frac{y}x)'=-x," and hence "\\frac{y}x=-\\frac{x^2}2+C." We conclude that "y=-\\frac{x^3}2+Cx" is the general solution of the differential equation.


Need a fast expert's response?

Submit order

and get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

Comments

No comments. Be the first!

Leave a comment

LATEST TUTORIALS
New on Blog